Influence of mild alkaline treatment on the cellulosic surfaces active sites - Ashori, Alireza (2021)
Agro-residues fibers are inexpensive environmentally friendly alternatives to synthetic fibers in fiber reinforced polymer composites. The natural fiber properties and bondability with adhesive can be modified by subjecting the fibers to a pre-treatment procedure. The knowledge ofthe modified fibers sur face properties is essential to explain and predict their applications. The present study is focused on the effect of alkaline treatment on the surface characteristics of stalk fibers from rapeseed, tobacco, cotton, lemon balm and kiwi. The chemical composition of fibers and Fourier transform infrared spectroscopy show components extraction and the X-ray diffraction show improvement in the crystallinity index of the treated fibers. But only the IGC analysis allows us to know in detail the alterations on the fiber surface and the effect on the adhesion of the fibers. IGC shows that alkaline treatment produces changes in the nature and number of the active sites, responsible for the physico-chemical activity of the surface of the fibers. The fiber hydrophobicity was improved by the increase of more energetic and active sites in the surface. Also,the creation of new basic active sites and removal of acidic active sites from the fiber surface due to alkaline treatment has been clearly shown.